COTAXTLA 1 UNA NUEVA VARIEDAD DE JITOMATE PARA LAS LLANURAS DE VERACRUZ - RICHARDSON, RALPH (My University, 1958)
si
CAMPO
Keywords: COTAXTLA 1, NUEVA, VARIEDAD, JITOMATE, LLANURAS, VERACRUZ; CIENCIAS AGRARIAS; AGRONOMIA; PRODUCCION DE CULTIVOS